Network Monitoring System for Light-rail Vehicle Based on CANopen Protocol - SONG Xi-zheng (机车电传动)
Software & hardware platform of light-rail vehicle network monitoring system based on CANopen protocol was introduced. Software & hardware design of CANopen main & slave device nodes was described in detail, and CANalyzer was used to analyzed CANopen network data stream. The light-rail vehicle network monitoring system was proved satisfy actual control application requirement.